GHRH excess and blockade in X-LAG syndrome. Issue 3 (15th December 2015) - Daly, Adrian F; Lysy, Philippe A; Desfilles, Céline; Rostomyan, Liliya; Mohamed, Amira; Caberg, Jean-Hubert; Raverot, Veronique; Castermans, Emilie; Marbaix, Etienne; Maiter, Dominique; Brunelle, Chloe; Trivellin, Giampaolo; et al.
Abstract : X-linked acrogigantism (X-LAG) syndrome is a newly described form of inheritable pituitary gigantism that begins in early childhood and is usually associated with markedly elevated GH and prolactin secretion by mixed pituitary adenomas/hyperplasia. Microduplications on chromosome Xq26.3 including the GPR101 gene cause X-LAG syndrome. In individual cases random GHRH levels have been elevated. We performed a series of hormonal profiles in a young female sporadic X-LAG syndrome patient and subsequently undertook in vitro studies of primary pituitary tumor culture following neurosurgical resection. The patient demonstrated consistently elevated circulating GHRH levels throughout preoperative testing, which was accompanied by marked GH and prolactin hypersecretion; GH demonstrated a paradoxical increase following TRH administration. In vitro, the pituitary cells showed baseline GH and prolactin release that was further stimulated by GHRH administration. Co-incubation with GHRH and the GHRH receptor antagonist, acetyl-(d -Arg 2 )-GHRH (1-29) amide, blocked the GHRH-induced GH stimulation; the GHRH receptor antagonist alone significantly reduced GH release. Pasireotide, but not octreotide, inhibited GH secretion. A ghrelin receptor agonist and an inverse agonist led to modest, statistically significant increases and decreases in GH secretion, respectively. GHRH hypersecretion can accompany the pituitary abnormalities seen in X-LAG syndrome. These data suggest that the pathology of X-LAG syndrome may include hypothalamic dysregulation of GHRH secretion, which is in keeping with localization of GPR101 in the hypothalamus. Therapeutic blockade of GHRH secretion could represent a way to target the marked hormonal hypersecretion and overgrowth that characterizes X-LAG syndrome.